Mast cells in asthma – state of the art. Issue 2 (February 2016) - Bradding, P.; Arthur, G.
Summary: Mast cells (MCs) play a central role in tissue homoeostasis, sensing the local environment through numerous innate cell surface receptors. This enables them to respond rapidly to perceived tissue insults with a view to initiating a co‐ordinated programme of inflammation and repair. However, when the tissue insult is chronic, the ongoing release of multiple pro‐inflammatory mediators, proteases, cytokines and chemokines leads to tissue damage and remodelling. In asthma, there is strong evidence of ongoing MC activation, and their mediators and cell–cell signals are capable of regulating many facets of asthma pathophysiology. This article reviews the evidence behind this.